Penentuan Kadar Logam Fe pada Air Sumur di Kota Padang dengan Metode Spektrometri Serapan Atom (SSA) - Intan Anika Putri; Rahadian Zainul (Lembaga Yasin AlSys, 2025)
Well water is a primary water source for communities and is vulnerable to contamination by heavy metals, particularly iron (Fe), which, at high concentrations, can cause organoleptic issues such as unpleasant odor, taste, and color, as well as pose health risks. According to Indonesian Ministry of Health Regulation No. 32 of 2017, the maximum allowable Fe content in water is 1 mg/L. This study aims to determine the concentration of Fe in well water samples from Padang City and evaluate the analytical data quality using Atomic Absorption Spectrometry (AAS). Water samples were collected and preserved with HNO₃ to maintain pH < 2, then analyzed using AAS at a wavelength of 248.3 nm. Method performance evaluation showed reliable analytical quality, with a calibration curve coefficient of determination (R²) of 0.9958, indicating excellent linearity. Accuracy validation through spike tests yielded recovery values within the acceptable range (85%–115%). However, the Relative Percent Difference (RPD) of duplicate samples indicated relatively high variability in precision (14.667%–26.415%), suggesting a need for optimization in the sample preparation stage. Despite this, precision in spike quality control showed excellent results, with an RPD of 0.221%. Quantitative analysis showed that all well water samples had Fe concentrations below the instrument detection limit, indicating compliance with water quality standards and general safety for sanitation and hygiene purposes.